2017
DOI: 10.1093/mnras/stx1459
|View full text |Cite
|
Sign up to set email alerts
|

Vertical structure of the near-surface expanding ionosphere of comet 67P probed by Rosetta

Abstract: The plasma environment has been measured for the first time near the surface of a comet. This unique data set has been acquired at 67P/Churyumov-Gerasimenko during ESA/Rosetta spacecraft's final descent on 2016 September 30. The heliocentric distance was 3.8 au and the comet was weakly outgassing. Electron density was continuously measured with Rosetta Plasma Consortium (RPC)-Mutual Impedance Probe (MIP) and RPC-LAngmuir Probe (LAP) during the descent from a cometocentric distance of 20 km down to the surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 44 publications
5
52
0
Order By: Relevance
“…Therefore, in order to quantify the CIR impacts on the cometary plasma density variation, the cometary ionosphere dependence on these parameters should first be isolated and removed. First, regarding cometocentric distances, the near-cometary plasma density is shown to follow a r −1 c variation (Edberg et al 2015;Heritier et al 2017). Second, regarding latitude and longitude variations, it is suggested that during the last four months of the Rosetta mission operation, considered for this work, the local outgassing rate was most intense over the southern hemisphere where CO 2 was a major species, while H 2 O dominated over the northern hemisphere (Gasc et al 2017;Heritier et al 2018).…”
Section: What Is the Cometary Plasma Response To The Cir Impact?mentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, in order to quantify the CIR impacts on the cometary plasma density variation, the cometary ionosphere dependence on these parameters should first be isolated and removed. First, regarding cometocentric distances, the near-cometary plasma density is shown to follow a r −1 c variation (Edberg et al 2015;Heritier et al 2017). Second, regarding latitude and longitude variations, it is suggested that during the last four months of the Rosetta mission operation, considered for this work, the local outgassing rate was most intense over the southern hemisphere where CO 2 was a major species, while H 2 O dominated over the northern hemisphere (Gasc et al 2017;Heritier et al 2018).…”
Section: What Is the Cometary Plasma Response To The Cir Impact?mentioning
confidence: 88%
“…The model uses time-varying electron-impact ionization frequency based on RPC-IES measurements, photoionization frequency obtained from Thermosphere Ionosphere Mesophere Energetics and Dynamics-Solar EUV Experiment (TIMED-SEE, Woods et al 2005) and interpolated to comet 67P along with cometary neutral density and neutral composition measured by the ROSINA-COPS (Rosetta Orbiter Spectrometer for Ion and Neutral Analysis-COmet Pressure Sensor) and ROSINA-DFMS (Double Focusing Mass Spectrometer) instruments (Balsiger et al 2007), respectively. The respective contributions of photoionization and electron-impact ionization are reported to be highly variable (see Galand et al 2016;Heritier et al 2017;Hajra et al 2017b).…”
Section: What Is the Source Of The Large Cometary Plasma Enhancement mentioning
confidence: 99%
“…We note that a similar but much simplified approach was used in the analysis of the final descent of Rosetta orbiter to comet 67P at the end of the mission operations on 2016 September 30 Heritier et al (2017). However, a much lower final time resolution (from about 70 ms to 4 s, varying in time) was used, assuming both isothermal electrons and constant photoelectron current collection at the spacecraft over the full-day descent instead.…”
Section: High Time-resolution Density Measurements From Rpc-mip and Rmentioning
confidence: 99%
“…Since in a plasma the n e ∼ n i we can use the same formula to find the appropriate fit for ion and electron current. To derive the density from the potential measurement, VV mode, we use that the spacecraft potential is related to plasma density as (Odelstad et al 2017;Heritier et al 2017)…”
Section: Lap-mip Cross Calibrationmentioning
confidence: 99%